Detection of rice seed vigor by low-field nuclear magnetic resonance - Song, Ping; Song, Peng; Yang, Hongwei; Yang, Tao; Xu, Jing; Wang, Kaitian (International Journal of Agricultural and Biological Engineering, 2018)
A new method to predict the seed vigor of rice was developed to control adulteration during the seed trading process and to address the deficiencies of traditional manual detection methods. Low-field nuclear magnetic resonance (LF-NMR) technique was used to detect the vigor of rice seeds. Four varieties (Beijing-1, Qianchonglang-2, Yanfeng-47 and Shennong-265) of rice seeds from the Rice Research Institute of Shenyang Agricultural University were chosen for the experiment. The transverse relaxation time T2, T21 and T22 were observed in the experiment. The peak start time of free water (transverse relaxation time T22), signal amplitude of bound water (transverse relaxation time T21), and moisture content decreased with the decrease in the vigor of the seeds. There were no obvious trends observed for the top of the peak and the end point of the transverse relaxation time T22. In addition, the start, top, and end time of the peak (transverse relaxation time T21), and the signal amplitude of bound water showed no consistent changes. The results indicated that LF-NMR could be used as a method to distinguish the vigor of rice seeds rapidly. This study provided theoretical basis and technical support for the rapid detection of rice seed vigor. Keywords: nondestructive detection, nuclear magnetic resonance, transverse relaxation time, signal amplitude, rice, seeds vigor DOI: 10.25165/j.ijabe.20181106.4323 Citation: Song P, Song P, Yang H W, Yang T, Xu J, Wang K T. Detection of rice seed vigor by low-field nuclear magnetic resonance. Int J Agric & Biol Eng, 2018; 11(6): 195–200. (6): 195–200.